Answer:
[tex]x=1[/tex]
Step-by-step explanation:
[tex]6\left(x-3\right)+10=2\left(4x-5\right)[/tex]
We'll use the distributive property to multiply 6 by (x-3):
[tex]6x-8 +10=2(4x-5)[/tex]
*Distributive property*, multiply 2 by (4x-4)
[tex]6x-8=8x-10[/tex]
Add 8 from both sides:
[tex]6x-8+8=8x-10+8[/tex]
[tex]6x=8x-2[/tex]
Subtract 8x from both sides:
[tex]6x-8x=8x-2-8x[/tex]
[tex]-2x=-2[/tex]
Divide both sides by -2:
[tex]\cfrac{-2x}{-2}=\cfrac{-2}{-2}[/tex]
[tex]x=1[/tex]
_____________________________